Are ohmic heating-treated whey dairy beverages an innovation? Insights of the Q methodology. (December 2020) - Coimbra, Lorena O.; Vidal, Vitor A.S.; Silva, Ramon; Rocha, Ramon S.; Guimarães, Jonas T.; Balthazar, Celso F.; Pimentel, Tatiana C.; Silva, Marcia C.; Granato, Daniel; Freitas, Mônica Q.; Pollonio, Marise A.R.; Esmerino, Erick A.; et al.
Abstract: The conceptual representation and consumer sensory profiling (100 consumers) of acerola flavored whey beverages manufactured using ohmic heating at different operational conditions were investigated using the Q methodology, having in mind the concept of Innovation with additional hedonic test and sensory description of the samples. In addition, the food technology neophobia questionnaire was also applied. Samples processed by increasing voltage gradient and frequencies presented higher overall liking and where associated to the innovation concept, being associated to typical sensory attributes as sweet taste, acerola color, thinner, refreshing, acerola aroma and acerola taste. Food Neophobia Technology Questionnaire showed that there is a more receptivity of the emerging technologies showing positive aspects regards the environmental and benefits obtained for them. The results of this study are useful to select ohmic heating parameters to be used in acerola flavored whey beverages and to guide dairy processors to build an effective strategy of commercialization of dairy beverages processed by emerging technologies. Highlights: Q methodology to obtain the sensory profile of ohmic heating-treated whey beverages. Q methodology and the conceptual profile of food submitted to emerging technologies. Innovation concept and overall liking associated to ohmic heating-treated products. Ohmic heating processing preserved the typical sensory attributes of whey beverages. Emerging technologies considered trustworthy and environmental-friendly.